Isolasi dan Karakterisasi Β-1,3-Glukanase Akar Semai Tusam (Pinus merkusii Jungh. et de Vriese) yang Berasosiasi dengan Fungi Ektomikorisa - M. D. Anggoro; S. M. Widyastuti; S. Margino (Universitas Gadjah Mada, 2005)
Association between tusam (Pinus merkusii Jungh. et de Vriese) seedling roots with ectomycorrhiza fungi was expected to increase the activity β-1,3-glucanase level in the plants. This enzyme has potency to protect seedling from soil borne fungal pathogens by degrading the fungal cell walls. The objectives of this research were to isolate and characterize β-1,3-glucanase from tusam seedling roots associated with ectomycorrhiza fungi. Crude protein was isolated with ammonium sulfat precipitation and then purified by gel filtration chromatography and characterize molecular weight, temperature and pH for optimum the activity. The enzyme from tusam seedling roots associated with ectomycorrhizal fungi, designated as GLUC15 have 15 kD molecular weight, 30° - 40° C temperature and pH 5-7 for optimum activity.",